Pengajuan Analisa Marketing Mix-4p Terhadap Purchase Intention Produk Aqua Di Dki Jakarta - Airin Anggraeni Sutedjo (Universitas Tarumanagara, 2019)
This research aims to analyze the effect Marketing Mix-4P on consumer’s Purchase Intention towards Aqua Product in DKI Jakarta. Data used in this research were obtained from questionnaires (primary). Sampling Methods used in this study using the Non-Probability Sampling Method, in which each element in the population does not have the opportunity or the same opportunity to be selected as a sample. The technique used is Convenience Judgment Sampling because the respondents selected are respondents who are willing and can help answer the research questions asked. To facilitate the study, the researcher has determined the criteria to be used in the sample selection in this research. The sample used by the researcher is people who live in DKI Jakarta province. Research findings show that the four Marketing Mix variables used in this study, Price, Product, and Promotion variables have a significant effect on Aqua Product Purchase Intention. Meanwhile, the Marketing Mix variable that does not provide significant impact to Aqua Product Purchase Intention is Place. The contribution of the four Marketing Mix variables included in the analysis model of the Purchase Intention of Aqua Products is 47.3% and the rest of 52.7% is influenced by other factors not tested in this study.